Perovskita de estanato de estrôncio dopada com níquel como catalisador para síntese de bio-óleo - Dantas Filho, Augusto (2012)
The reactions of deoxygenation fatty acids are widely used for production of biofuels, using temperatures ranging from 300-350 °C. The purpose of this work was to prepare and characterize the catalyst SrSn0,9Ni0,1O3 applied in decarboxylation of stearic acid to obtain bio-oil. The strontium stannate (SrSnO3) orthorhombic perovskite is widely studied due to their technological applications and is now being widely used in catalysis. In this work, the SrSnO3 pure and doped with 10 mol % nickel (SrSnO3, SrSn0,9Ni0,1O3) were synthesized by the polymeric precursor method. The solids were characterized by the techniques of thermal analysis (TG/DTA), infrared spectroscopy (IR) spectroscopy of the ultraviolet-visible, micro-raman spectroscopy, X-ray diffraction (XRD) and surface area by the BET method . The materials obtained showed SrCO3 as the secondary phase, with the addition of nickel in the structure increased the formation of carbonate as the results of thermogravimetry (TG) and infrared spectroscopy, and still caused a disruption long and short range, according to the data of micro-Raman spectroscopy and XRD. The catalyst SrSn0,9Ni0,1O3 used in catalytic decarboxylation reaction of stearic acid at 340 °C in H2 atmosphere showed activity for the major product (heptadecane) but not proved to be due to the selective formation of octadecenos in greater quantity. There was a trend to higher conversion of stearic acid to lower concentrations of H2.